Staphylococcus aureus Alpha-Toxin Limits Type 1 While Fostering Type 3 Immune Responses - Bonifacius, Agnes; Goldmann, Oliver; Floess, Stefan; Holtfreter, Silva; Robert, Philippe A.; Nordengrün, Maria; Kruse, Friederike; Lochner, Matthias; Falk, Christine S.; Schmitz, Ingo; Bröker, Barbara M.; Medina, Eva; et al. (Frontiers in Immunology, 2020)
Staphylococcus aureus can cause life-threatening diseases, and hospital- as well as community-associated antibiotic-resistant strains are an emerging global public health problem. Therefore, prophylactic vaccines or immune-based therapies are considered as alternative treatment opportunities. To develop such novel treatment approaches, a better understanding of the bacterial virulence and immune evasion mechanisms and their potential effects on immune-based therapies is essential. One important staphylococcal virulence factor is alpha-toxin, which is able to disrupt the epithelial barrier in order to establish infection. In addition, alpha-toxin has been reported to modulate other cell types including immune cells. Since CD4+ T cell-mediated immunity is required for protection against S. aureus infection, we were interested in the ability of alpha-toxin to directly modulate CD4+ T cells. To address this, murine naïve CD4+ T cells were differentiated in vitro into effector T cell subsets in the presence of alpha-toxin. Interestingly, alpha-toxin induced death of Th1-polarized cells, while cells polarized under Th17 conditions showed a high resistance towards increasing concentrations of this toxin. These effects that could neither be explained by differential expression of the cellular alpha-toxin receptor ADAM10 nor by differential activation of caspases, but might results from an increased susceptibility of Th1 cells towards Ca2+-mediated activation-induced cell death. In accordance with the in vitro findings, an alpha-toxin-dependent decrease of Th1 and concomitant increase of Th17 cells was observed in vivo during S. aureus bacteremia. Interestingly, corresponding subsets of innate lymphoid cells and γδ T cells were similarly affected, suggesting a more general effect of alpha-toxin on the modulation of type 1 and type 3 immune responses. In conclusion, we have identified a novel alpha-toxin-dependent immunomodulatory strategy of S. aureus, which can directly act on CD4+ T cells and might be exploited for the development of novel immune-based therapeutic approaches to treat infections with antibiotic-resistant S. aureus strains.